Medium Specificities of The Strange Case of Dr Jekyll and Mr Hyde by Robert Louis Stevenson: Marvel Comic, Video Game, and Korean TV Drama - Edria Sandika (Vivid: Journal of Language and Literature, 2020)
This study analyzes Medium Specificities found in the adaptations of The Strange Case of Dr Jekyll and Mr Hyde  This study uses Linda Hutcheon’s theory of adaptation focuses on medium specificity in engaging audiences and the process of repetition but not replication. This study found three adaptation works of Dr Jekyll and Mr Hyde fulfilled the process of repetition but not replication from their textual transformations and innovations occurred in the works.